Cogwheels for generation of surface plasmon polariton vortex - Xu, Zhengji (2016)
We propose a cogwheel structure formed by an air ring and equally distributed air cogs along the ring on a gold film for generation of surface plasmon polariton vortex. We show that a well-designed cogwheel can generate an optical vortex-like response and that the characteristics of such SPP vortex are directly related to cogwheel geometries and can be controlled by adjusting the polarisation direction of incident light.